Pectin-iron capsules: Novel system to stabilise and deliver lactic acid bacteria - Ghibaudo, María Florencia (2017)
The delivery of probiotics has been a challenge because microorganisms must overcome harmful environments both at a technological and at a physiological level. Encapsulation is one of the strategies to protect microorganisms against both problems. This work aimed at encapsulating probiotic Lactobacillus plantarum CIDCA 83114 in pectin-iron beads obtained by ionotropic gelation, enabling bacteria safe delivery and providing a source of iron and fibre. Microorganisms in the stationary phase were suspended in a 4% w/v pectin solution at pH 5, and the suspension, dripped into a 150 mM FeSO4 solution. The beads were freeze-dried and stored for 60 days at 4 °C. The morphology of the beads was observed by scanning electron microscopy. Bacterial culturability was determined after freeze-drying, and after the exposure to simulated saliva, gastric and intestinal conditions. The iron and pectin releases were also investigated in the same digestive conditions. Microorganisms were fully entrapped in smooth and spherical pectin-iron beads of ca. 1–2 mm diameter. Bacterial culturability did not decrease during storage. Encapsulation protected microorganisms against simulated digestive conditions, also enabling the complete release of iron and pectins in the gut. The results obtained support the safe delivery of both probiotic bacteria and iron to the gut. As iron deficiency still continuous to be a worldwide problem, using iron-pectin beads could be an adequate strategy to functionalise food products, contributing to attain the recommended iron intake.